The effect of work stressors on employee stress and creativity mediated by employee personality at Sukoharjo Regional General Hospital - Putri, Fidela Berliani Prasaja (Institute of Computer Science (IOCS), 2025)
This study aims to test the personality in moderating stressor and stress relationships and the relationship of stress and creativity. The occurrence of stress due to the factors that trigger stress (stressor) has a significant relationship to create an idea of creativity with the personality as a variable that moderate the relationship. Data obtained through questionnaires distributed to employees at RSUD Sukoharjo. The sampling technique used was cluster random sampling with a population of 21 sections scattered in the hospital with as many as 200 respondents. Hypothesis test is done by using regression analysis with moderator variable. The results of this study showed that stressor had significant effect on stress, stress had significant effect on creativity, stressor had no significant effect on stress after personality entered as moderating variable and stress had no significant effect on creativity after entering as moderation variable. This means that personality is not a moderating variable but an independent variable.